2009
DOI: 10.1111/j.1365-2710.2009.01108.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high dose ofN-acetylcysteine in lupus nephritis: a case report and literature review

Abstract: An imbalance of oxidative-antioxidant defence mechanism has been proposed in systemic lupus erythematosus patients. Co-administration of N-acetylcysteine (NAC) which has a strong antioxidant activity may produce a satisfactory therapeutic outcome when added to standard therapy. We report a case of a 46-year-old lupus nephritis patient who received 1800 mg of NAC orally. After NAC, this patient showed a higher glutathione level, and a normal level of malondialdehyde, a lipid peroxidation product. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…In line with this, SLE patients exhibit elevated levels of various markers of protein oxidiation and reduced activity of antioxidant enzymes (294). Administration of NAC, which serves as a GSH precursor, and of cysteamine has been found to improve the clinical outcome of murine lupus, since both compounds suppressed mortality of female SLE mice, and additionally NAC suppressed autoantibody formation (255,263). On this basis, a phase I-II NACbased clinical trial of SLE was launched, and after 1 year of treatment patients showed reduced disease severity and reduced muscle fatigue, the latter being the most disabling symptom for *50% of SLE patients (255).…”
Section: Chiurchiù and Maccarronementioning
confidence: 99%
“…In line with this, SLE patients exhibit elevated levels of various markers of protein oxidiation and reduced activity of antioxidant enzymes (294). Administration of NAC, which serves as a GSH precursor, and of cysteamine has been found to improve the clinical outcome of murine lupus, since both compounds suppressed mortality of female SLE mice, and additionally NAC suppressed autoantibody formation (255,263). On this basis, a phase I-II NACbased clinical trial of SLE was launched, and after 1 year of treatment patients showed reduced disease severity and reduced muscle fatigue, the latter being the most disabling symptom for *50% of SLE patients (255).…”
Section: Chiurchiù and Maccarronementioning
confidence: 99%
“…High doses of NAC have been demonstrated to frequently cause adverse effects (16), and the dose of 4.8 g/day used in the study by Lai et al (14) caused certain uncomfortable reactions. In a report by Tewthanom et al (8), NAC at the relatively high dose of 1.8 g/day was used to treat a patient with an LN-history of several years and achieved a satisfactory therapeutic outcome. In the present study, considering that the two cases were early-stage LN and that a high dose of NAC may have caused a higher risk of adverse effects (16), the moderate dose of NAC at 1.2 g/day was selected, to be administered in combination with the basic treatment using hydroxychloroquine and calcitriol (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The NAC effervescent tablet was dissolved in warm water and taken twice a day, at a dose of 600 mg each time. The 3-month (12-week) intervention was decided according to a previous study (8). The routine blood and urine, 24-h urine protein,…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased intracellular glutathione levels in the various blood components, including total lymphocytes and its subsets (CD4, CD8 T cell) are strongly associated with disease severity and linked to increase Th1/Th2 cytokine imbalance and lymphocyte apoptosis in SLE patients (Shah et al, 2011a). Similarly, Tewthanom et al (2009) reported that administration of NAC may be beneficial in mild SLE patients in terms of decreasing lipid peroxidation. Lai et al (2012) demonstrates that GSH regulates the elevation of mitochondrial transmembrane potential (∆ψ m ) or Mitochondrial Hyperpolarization (MHP), which in turn activates the mammalian Target Of Rapamycin (mTOR) in lupus T cells.…”
mentioning
confidence: 99%